‘Memristive’ switches enable ‘stateful’ logic operations via material implication - Borghetti, Julien; Snider, Gregory S.; Kuekes, Philip J.; Yang, J. Joshua; Stewart, Duncan R.; Williams, R. Stanley (Nature (London), 2010)
A good memory for logic The possibility of combining the electrical properties of a memory element and a resistor — in a memristor or memristive device — was proposed by Leon Chua in 1971. It remained in the realms of theory until two years ago, when bipolar voltage-activated switches were identified as physical realizations of the memristor. The resulting revival of interest in memristive devices looks set to continue now that Julien Borghetti and colleagues show how 'memristors' can also perform a fundamental class of logic operations that requires individual devices to act simultaneously as logic and memory elements. A challenge in the semiconductor industry is to create integrated circuits that use new physical state variables — other than charge or voltage — to offer memory and logic functions. Memristive devices, which combine the electrical properties of a memory element and a resistor, use resistance instead, and here such 'memristors' are shown to perform logic operations as well. The authors of the International Technology Roadmap for Semiconductors 1 —the industry consensus set of goals established for advancing silicon integrated circuit technology—have challenged the computing research community to find new physical state variables (other than charge or voltage), new devices, and new architectures that offer memory and logic functions 1 , 2 , 3 , 4 , 5 , 6 beyond those available with standard transistors. Recently, ultra-dense resistive memory arrays built from various two-terminal semiconductor or insulator thin film devices have been demonstrated 7 , 8 , 9 , 10 , 11 , 12 . Among these, bipolar voltage-actuated switches have been identified as physical realizations of ‘memristors’ or memristive devices, combining the electrical properties of a memory element and a resistor 13 , 14 . Such devices were first hypothesized by Chua in 1971 (ref. 15 ), and are characterized by one or more state variables 16 that define the resistance of the switch depending upon its voltage history. Here we show that this family of nonlinear dynamical memory devices can also be used for logic operations: we demonstrate that they can execute material implication (IMP), which is a fundamental Boolean logic operation on two variables p and q such that p IMP q is equivalent to (NOT p )OR q . Incorporated within an appropriate circuit 17 , 18 , memristive switches can thus perform ‘stateful’ logic operations for which the same devices serve simultaneously as gates (logic) and latches 19 (memory) that use resistance instead of voltage or charge as the physical state variable.